Rasmussens Encephalitis: Report of 2 Cases (Journal of Dhaka Medical College, 2010)
Two boys, one was 7 years and the other was 3 years 7 months old, were admitted into Dhaka Medical College Hospital one year apart with almost similar complaints of intractable partial seizure, progressive hemiparesis and cognitive deterioration following an episode of encephalitis. Developmental milestones was age appropriate till occurrence of encephalitis, thereafter started deteriorating with progressive deterioration of cognition, behavior, learning, memory and speech. Different anticonvulsants were tried in optimal doses, yet seizure remained uncontrolled. After admission CSF study, EEG and brain imaging was done. EEG showed unilateral slow waves and MRI revealed unilateral cortical atrophy with hyper intense signals in T2 and FLAIR. According to European consensus statement both cases were diagnosed as Rasmussen's Encephalitis (RE). Key words: Rasmussen's Encephalitis; hemispheric atrophy; seizure. DOI: 10.3329/jdmc.v18i2.6283 J Dhaka Med Coll. 2009; 18(2) :178- 182